Perlindungan Hukum Terhadap Desain IndustriDi Sukoharjo - PUTRO, HARY SUHUD SUNARYO; , Prof. Dr. Absori, S.H.,M.Hum; , Inayah, S.H (2015)
Legal Protection of Industrial Design in Sukoharjo.Hary Suhud Sunaryo Putro. C 100 090 115. Faculty of Law, Muhammadiyah University of Surakarta ABSTRACT The research is titled "Legal Protection of Industrial Design in Sukoharjo". Purposes of the research are to describe an industrial design and its legal protection, especially in Sukoharjo region and to know formulation of legal protection model attached in the industrial design. The research is a descriptive one because it reveals actual facts of legal protection for industrial design viewed from Act No. 31 of 2000. Based on results of discussion, it can be concluded that: (1) almost all furniture producers and craftsmen of Sukoharjo region had no official legal protection from Copyright Body, especially in industrial design, because they were not paying attention about it. For them, if they earned enough daily living and their family needs were met, it was no problem. (2) procedures of applying for industrial design copyright in Sukoharjo was basically in line with what has been determined in Act No. 31 Article 18 of 2000 about Industrial Design. However, there was no one applying for the legal protection at all. (3) Future model of legal protection for industrial design should be enforcement of authorized institution of copyright, especially in industrial design by making more socializations about advantages and disadvantages of applying for industrial design copyright. Key words: Legal Protection, Industrial Design, Furniture Producers in Sukoharjo